Adult onset Still's disease and viral infections. - Wouters, J M (1988)
Several micro-organisms, especially viruses, have been associated with juvenile and adult onset Still's disease. In the present study a search for probable triggering viral infections in five consecutive patients with early, active adult onset Still's disease has been made. In one patient echovirus 7 was identified as a probable triggering agent. Evidence of infection with this virus was acquired by virus cultures and serological tests. In two patients the illness was probably initiated by a rubella reinfection. Both had initially high stable monospecific IgG antibody titres but no IgM antibodies to this virus. In the remaining two cases no particular triggering viral infection could be designated. Evidence of a viral infection was thus found in three of these five patients. Adult onset Still's disease may represent a reaction pattern to certain infections.